Isolated left diaphragm metastasis of rectum adenocarcinoma - Yıldırım, Mustafa; Koc, Mustafa (My University, 2020)
Isolated diaphragm metastasis from colorectal cancer is very rare. In our literature review, it was seen that 3 cases have been reported. One of these cases was originatedfrom rectal cancer. Others were originated from the ascending colon and sigmoid colon. In the literature cases, isolated diaphragm metastasis was adjacent to the liverand in the right diaphragm. We present a case with isolated left diaphragm metastasis originating from rectum adenocarcinoma, which has not been previously reportedin the literature.
Keywords: Onkoloji; Cerrahi